“Dependency worker”: ruolo e valore di una nozione a partire da Eva Feder Kittay - Damonte, Marco (Filosofia Morale/Moral Philosophy, 2024)
“Dependency worker”: role and value of a notion starting with Eva Feder Kittay More than twenty-five years after the publication of Kittay’s Love’s Labor. Essays on Women, Equality, and Dependency, it is desirable to reread this text through the notion of dependency worker. With reference to this concept, it is possible to grasp some original aspects of Kittay’s reflection neglected by secondary literature that go beyond the classic setting of an ethic of care, but which prove to be useful in providing a contribution both to feminist philosophy and to disability studies. After an adequate contextualization of Kittay’s book and some clarifications on the style in which the arguments are presented, I will identify the starting point of Kittay’s reflections in the anthropological notion of vulnerability, understood in an ontological dimension. Precisely because of the vulnerability that constitutes human beings, each person must be considered “some mother’s child” and treated accordingly. Thanks to the notion of vulnerability, the dependency work assumes a particular importance which I will highlight by providing an adequate definition, a basic classification and indicating its main characteristics. Considering the current conceptions of justice and equality inadequate to the needs of dependency work, Kittay proposes to abandon the current welfare model and move to a model based on “doulia”. I will conclude by suggesting the usefulness of Kittay’s reflection on dependency work to appreciate and enhance the legislative proposal for the protection of the “family caregiver” currently under discussion in the Italian parliament.